Comparison of Change in Hindfoot Alignment with Coleman Block Testing Using Clinical Exam, X-ray, and Weight-bearing CT. Issue 4 (22nd October 2020) - Foran, Ian; Mehraban, Nasima; Jacobsen, Stephen K.; Bohl, Daniel D.; Hamid, Kamran S.; Lin, Johnny L.; Lee, Simon
Category: Hindfoot; Midfoot/Forefoot Introduction/Purpose: The Coleman block test has traditionally been used to distinguish between forefoot- and hindfoot-driven deformity as well as flexibility of cavovarus deformity. However, there has been no validation of the Coleman block test using x- rays or weightbearing CT scan. The purpose of this study was to compare hindfoot alignment in cavovarus feet with and without the Coleman block using clinical exam, x-ray, and weightbearing CT scan. Methods: We retrospectively evaluated 7 feet in 7 patients. The average age was 57, there were 5 males, and the average BMI was 34.7. Average calcaneal pitch was 30 degrees. Clinical measurements were made using standing talocalcaneal angle (STCA) and resting calcaneal stance position (RCSP) with and without a Coleman block using a camera positioned at 0 degrees to the heels. Hindfoot angle (HFA) was measured off of Saltzman-view x-rays and off of weightbearing CT coronal reconstructions with and without the Coleman block. Finally, foot ankle offset (FAO) was measured with and without the Coleman block from weightbearing CT using Cubeview TALAS software. Differences before and after Coleman block were measured using paired t- testing and correlations between different hindfoot alignment measurements were made using Pearson correlation coefficients. Results: The average change in STCA before and after Coleman block placement was 2.9 degrees (7.14 varus without block, 4.28 degrees of varus with block; p<0.05). The average change in hindfoot angle before and after Coleman block using X-ray was 7.4 degrees (14 degrees varus without block, 6 degrees varus with block; p=0.08), and using CT was 3.9 degrees (14 degrees varus without block, 10 degrees varus with block; p= 0.06). There was no significant change in FAO before and after Coleman block testing. STCA was best-correlated with FAO (R= 0.7, p<0.05). CT HFA was also well-correlated with FAO (R=0.68, p<0.05). There was lesser correlation between X-ray HFA and FAO (R=0.608, p<0.05) and X-ray HFA and SCTA (p=0.63, p<0.05). Conclusion: Although Coleman block testing resulted in a decrease in varus, no patient had full re-constitution of physiologic hindfoot valgus with any measurement method. This suggests that either the forefoot was a partial (but never a complete) 'driver' of hindfoot varus deformity, or that there was some degree of rigidity in all patients tested. FAO did not demonstrate a statistically significant difference with and without Coleman block on this small sample size. FAO was best correlated with both clinical exam and CT HFA measurements. Clinical exam and weightbearing CT may be more reliable than radiographs in measuring cavovarus hindfoot alignment. Figure 1.